There are at least 8 ways Beckman pH control saves money, saves time, saves waste in textile operations! - Beckman Instruments, Inc. (1950)
Arnold Beckman invented his first pH meter in 1934 at the request of a chemist from the California citrus industry, who needed an accurate way to measure the acidity of his product. The resulting instrument kicked off rapid development not only of Beckman Instruments, Inc. but also of the electronic scientific instrument industry.
Keywords: Textile industry--Technological innovations; Hydrogen-ion concentration--Measurement--Instruments; Scientific apparatus and instruments; Hydrogen-ion concentration; Beckman Instruments, Inc.